The Variance of Non-Parametric Treatment Effect Estimators in the Presence of Clustering - Hanson, Samuel G.; Sunderam, Adi (The Review of Economics and Statistics, 2012)
Nonparametric estimators of treatment effects are often applied in settings where clustering may be important. We provide a general methodology for consistently estimating the variance of a large class of nonparametric estimators, including the simple matching estimator, in the presence of clustering. Software for implementing our variance estimator is available in Stata.